IMPROVING YIELD AND YIELD QUALITY OF FOUR FABA BEAN CULTIVARS GROWN UNDER RAINFALLS - Caser G. Abdel (Mesopotamia Journal of Agriculture)
Four experiments were carried out at the research field of horticulture Dept, Agriculture & Forestry college, Mosul University, during 2004-2005 growing season to investigate the ability of boosting drought resistance in four faba bean cultivars by foliar spraying of alar (B9) at rates of 0, 250, 500, 750 and 1000 mg. L‾¹.; cultar (ppp3) at rates of 0, 50, 75 and 100 mg L‾¹; indole-3-butyric acid (IBA) at rates of 0, 50, 75 and 100 mg. L‾¹ and naphthalene acetic acid at rates of 0, 25, 50 and 75 mg. L‾¹ at the commence of flowering and was repeated after 2 weeks. Experiment 1 , 250 mg. L‾¹ alar was the most effective treatment in enhancing drought resistance of Aquadulce cultivar. It increased yield of dry seeds (52.8%). Furthermore, it improved stomata behaviors to sustain gas exchange good through increasing stomata populations and reducing their aperture dimensions. Experiment 2 results exhibited that 50 mg. L‾¹ cultar rate was the most suitable treatment for increasing drought resistance of Local Syrian cultivar. It gave dry seed yield increases of 48.4%, in relation to check. In addition to that it highly modified stomata dimensions to improve gases exchanges. Experiment 3 results displayed that 75 mg.L‾¹ IBA rate applied on Babylon cultivar was the most potent treatment in relation to untreated treatment. It substantially increased the yield of dry seeds (86.4%), when compared to untreated control. Finally, experiment 4 results revealed that the application of 25 mg.L‾¹ NAA on the determinate Taka357 cultivar showed profound increases in yield of dry seeds (30.5%), as compared to control.